Salt tolerance potential of native plant species and halophilic bacteria from Bahadur Khel and Khewra, Pakistan (Kuwait Journal of Science)
Soil salinity poses a significant challenge to agriculture, particularly in arid and semi-arid regions, necessitating innovative solutions for sustainable crop production. This study focused on characterizing the salinity tolerance of plants and associated microbial communities in two saline regions of Pakistan: Bahadur Khel and Khewra. Soil and plant samples were collected from these locations to assess their physicochemical properties, salinity tolerance, and elemental composition. Indigenous microbial strains were isolated, identified, and tested for salinity resistance. The soil samples were analyzed for electrical conductivity (EC), pH, soil texture, and nutrient content, while plant samples were assessed for their bioconcentration and translocation potential of osmoregulatory elements such as Na+, K+, Ca2+, and Mg2+. Results indicate that Khewra soil has moderate salinity, while Bahadur Khel displays strong salinity. Bacterial strains isolated from Khewra include Oceanobacillus picturae and Halobacillus sp., while Bahadur Khel contained Macrobacterium paludicola, Solibacillus silvestris, Bacillus cereus, and Arthrobacter luteolus. All strains demonstrated salt tolerance of 10–14 % NaCl. Most plant species exhibited a Na translocation factor of >1, demonstrating their ability to uptake and transport ions to the shoots, suggesting phytoextraction potential. Salsola kali, Salsola imbricata, and Paganum hermala accumulated Na in shoots, whereas Cenhrus pennisetiformis and Salsola imbricata in roots, indicating phytoaccumulation capacity. The underlying mechanisms of these halophytes and salt tolerant bacteria can help to promote the growth of glycophytic organisms in saline soils. © 2025 The Authors